An integrative approach to understand vulnerability and resilience post-disaster: The 2015 cyclone Pam in urban Vanuatu as case study. Issue 3 (5th June 2017) - Rey, Tony; Le De, Loic; Leone, Frederic; Gilbert, David
Abstract : Purpose: The purpose of this paper is to develop a multidimensional approach for effectively managing natural disasters; this paper has three research objectives. First, it provides an analysis on the hydro-geomorphological effects of the cyclone in the urban context. Second, it proposes an analysis for the vulnerability and resilience recovery of the populations living in urban areas. Third, it specifies the implications for sustainable recovery and longer-term disaster risk reduction. Design/methodology/approach: A detailed case study of the tropical cyclone Pam was carried out to identify hydro-geomorphologic effects and damages in an urban area and specific problems associated with managing natural disaster in Vanuatu. Findings: The investigations reveal that living in an urban area increases a population's exposure to hydrological, weather and sea-related risks. Whereas advice on cyclones seems to work very well, the coastal risks and floods seem to be underestimated with a very high exposure and vulnerability to risk. Pre-existing vulnerabilities were exacerbated after cyclone Pam. However, other communities have been able to reinforce their resilience through local initiatives. The government and outside aid were very quick to react, despite problems of coordination, exchange of information, communication and long-term strategy. Practical implications: The bottom-up, top-down, local and global approaches, applied on the time scales, should lead to actions that will reinforce the ability of the people of Vanuatu to adapt to high-energy events and to the effects of climate change. Originality/value: This paper highlights the importance of understanding how the urban communities are vulnerable to natural hazards and of strategies for increasing their resilience.